Abstacles To Implementing Hybrid Education In General Secondary Education Schools In The City Of Hama (Journal of Hama University, 2026)
The aim of the research was to reveal the obstacles to hybrid education in secondary schools in Hama city from the point of view of secondary school principals, as well as to reveal the differences between the average scores of the research sample members on the hybrid education obstacles questionnaire attributed to the research variables (academic qualification - training courses The research sample consisted of (86) male and female principals of secondary schools in Hama city. They were chosen using a simple random method. The descriptive analytical method was used, and the questionnaire was used as a tool for collecting data. The most important results reached by the research are the following:1- The obstacles to hybrid education in public secondary schools, from the point of view of secondary school principals, came to a large degree with an arithmetic mean of (3.78), and a percentage of (75.6%)2- The ranking of obstacles to hybrid education came as follows: The field (technical and financial obstacles) came in first place with an arithmetic mean of (3.89) and a percentage of (77.8%), followed by the field (educational obstacles) in second place with an arithmetic mean of (3.75) and a percentage of (75%), then the field (human obstacles) in third place with an arithmetic mean of (3.70) and a percentage of (74%).3- There are statistically significant differences at a significance level of (0.05) between the average answers of the research sample members to the questionnaire on obstacles to hybrid education, attributed to the variable of academic qualification, in favor of managers with higher academic qualifications4- There are no statistically significant differences at a significance level of (0.05) between the averages of the answers of the research sample members to the questionnaire on obstacles to hybrid education attributable to the training courses variable
Keywords: Hybrid Education - General Secondary Education Schools